Integrated serum pharmacochemistry, pharmacokinetics, and network analysis to explore active components of BuShao Tiaozhi Capsule on hyperlipidemia - Tang, Ruiyin; Xiao, Guanlin; Liu, Yanchang; Jia, Dezheng; Zeng, Zhihao; Jia, Canchao; Li, Dongmei; Li, Yangxue; Jiang, Jieyi; Li, Sumei; Bi, Xiaoli (Frontiers in Pharmacology, 2025)
BuShao Tiaozhi Capsule (BSTZC), a novel drug in China, has been used to treat hyperlipidemia (HLP) in clinical practice for many years. Despite our previous studies suggesting that BSTZC can treat HLP, there is a lack of a rapid and systematic method to explore its active components. Therefore, this study aimed to investigate the active components and mechanisms of BSTZC in treating HLP by integrating serum pharmacology, pharmacokinetics, network analysis, and experimental validation. We first established UPLC fingerprints, calibrated 23 common peaks, and identified 13 common peaks, and the similarity was greater than 0.99 for 10 batches. A total of 9 metabolites from BSTZC were identified in serum and considered as PK markers. The pharmacokinetics parameters of the PK markers were compared between the control group and the model group through the pharmacokinetics study to determine the dynamic changes of representative components in rats. Compared with the control group, the Cmax and AUC0→t of OXY, IVT, IVL, and KPF-3-G were significantly higher (P<0.05), the AUC0→∞ of OXY, PN, and IVT were significantly higher (P<0.05), the t1/2 of IVT, SA, and KPF-3-G were significantly different (P<0.05). In vivo experiments showed that BSTZC and its active components could effectively alleviate lipid metabolism disorders and liver injury, with obvious lipid-lowering effects. Further studies showed that BSTZC alleviated HLP by inhibiting the PI3K/Akt signaling pathway, which was consistent with the results of the network analysis study. Our results revealed the active components and mechanisms of BSTZC in the treatment of HLP, which could provide useful information to guide the clinical application of BSTZC.